2016
DOI: 10.1053/j.semperi.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Executive function in children born preterm: Risk factors and implications for outcome

Abstract: Executive function (EF) refers to the set of cognitive processes involved in the self-regulation of emotion and goal-directed behavior. These skills and the brain systems that support them develop throughout childhood and are frequently compromised in preterm children, even in those with broadly average global cognitive ability. Risks for deficits in EF in preterm children, and attendant problems in learning and psychosocial functioning, are higher in those with more extreme prematurity, neonatal complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 142 publications
(178 reference statements)
2
48
0
4
Order By: Relevance
“…Given that preterm birth and low birthweight are the leading causes of infant mortality and are associated with long-term cognitive developmental child and adult health issues, it is imperative to understand factors associated with these disparities (Farooqi, Adamsson, Serenius, & Hägglöf, 2016;Taylor & Clark, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Given that preterm birth and low birthweight are the leading causes of infant mortality and are associated with long-term cognitive developmental child and adult health issues, it is imperative to understand factors associated with these disparities (Farooqi, Adamsson, Serenius, & Hägglöf, 2016;Taylor & Clark, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Schoolchildren who are born very preterm, at up to 32 weeks of gestation and with very low birthweights (VLBW) of up to 1500 g, still face a relatively greater risk of impaired neurobehavioral outcomes, even if they do not have neurological abnormalities. These include deficits in cognition and executive function, as well as problems that affect their academic performance . Due to the gradual increase in survival rates of very preterm and VLBW children, there is growing concern that the number of children who develop learning problems and neurocognitive impairment will increase.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that executive dysfunction may mediate the relationship between preterm birth and below average academic achievement and social competence in young adulthood reported in the literature (Anderson et al, 2010;Burnett, Scratch, & Anderson, 2013;Kroll et al, 2017;Luu, Ment, Allan, Schneider, & Vohr, 2011). However, studies presented so far are inconclusive (Taylor & Clark, 2016). Nosarti and colleagues reported that among children born very preterm in the late 1970s and early 1980s, executive function deficits, identified at school age, persisted into young adulthood.…”
mentioning
confidence: 99%